The Sino-German λ6cm polarization survey of the Galactic plane. (5th March 2015) - Han, J. L.; Reich, W.; Sun, X. H.; Gao, X. Y.; Xiao, L.; Reich, P.; Shi, W. B.; Wielebinski, R.
Abstract : After Prof. R. Wielebinski visited China in 1999, we started to plan the Sino-German λ6 cm polarization survey of the Galactic plane, using the Urumqi 25-m radio telescope of Xinjiang (formerly Urumqi) Astronomical Observatory, Chinese Academy of Sciences. It is a high-frequency complement of previous Effelsberg 21-cm and 11-cm surveys, using the same observing and processing methods. The telescope is located at an altitude of 2029 m above sea level at geographic longitude of 87°E and latitude 43°N. The dual-channel λ6 cm receiver with a polarimeter and a bandwidth of 600 MHz was designed by O. Lochner and constructed at the MPIfR in Germany with involvements by the Urumqi engineers M.Z. Chen and J. Ma. In August 2004, the receiver was installed at the secondary focus of the Urumqi 25-m telescope.